Effectiveness of Shiva Gutika in Oligozoospermia – A Case Study: A Promising Ayurvedic Solution for Male Infertility (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Stress and lifestyle disturbances are the most dominating issues faced by people in present scenario which leads to deteriorating health of individuals. Infertility is one of the consequences of these imbalances. Out of total cases of infertility 30-40 account for male infertility. There are various anatomical and physiological reasons for male infertility and Oligozoospermia being the most common of all. Ayurveda has always proved itself to be miraculous in treating such health issues even in the present scenario and one such medicine from Ayurvedic classical literature is “Shiva Gutika”. The Gutika has been prepared pharmaceutically in standardised way as mentioned in Chakradutta. Shiva Gutika contains drugs having Rasayana and Vrishya properties and Shilajatu which is the main ingredient of Shiva Gutika is proven drug that works on improving and enhancing Shukra. The aim of the study was to compare effectiveness of the treatment in improving quality and quantity of Shukra. For which the study was carried out on 6 male patients for 60 days and effect was observed. Symptoms being Alpa Cheshta (Lack of Libido), Daurbalya (Fatigue) and Mukha Shosh (Dryness of mouth) and sperm count less than 15 million spermsml. The dose given was 500 mg BD with 500 ml of Luke warm milk after meals. After the completion of treatment the results were remarkable with subsidation of symptoms and notifiable rise in sperm count. It was then concluded that Shiva Gutika proved itself to be really effective in cases of Oligozoospermia and more rigorous studies are recommended for more elaboration.